KERENTANAN BERAS DARI PADI LOKAL DATARAN TINGGI ACEH TERHADAP HAMA PASCAPANEN Sitophilus oryzae L. (COLEOPTERA: CURCULIONIDAE) - Hendrival Hendrival; Khaidir Khaidir; Aulia Afzal; Rahmaniah Rahmaniah (Jurnal Agroteknologi, 2018)
The selection rice of resistant to pests S. oryzae can be done through the utilization of local paddy germplasm. The study aims to determine the level of resistance of local upland rice Aceh to against pest infestation S. oryzae. The results showed that the local paddy rice from upland Aceh has a level resistance from resistance until moderately to susceptible to pest infestations S. oryzae. The rice from varieties Depet classified in the category-resistant, while varieties Putih, Toa, and Bontok classified in the moderate category. Local rice upland Aceh from varieties Pulo Aceh and Tajuk classified in the category of moderate to susceptible to pest attack S. oryzae during storage rice. Results of correlation analysis showed that resistance rice local upland Aceh affected by moisture content (r = 0.864*; P<0.05). Results of correlation analysis showed that positive correlation non significant between resistance with characteristic dimensions of rice such as length (r = 0.106; P> 0.01), negative correlation non significant with wide (r = -0.339; P>0.01), and a positive correlation non significant with ratio (r = 0.167; P>0.01). The content of protein and moisture content of the rice had a positive correlation with the population of adult S. oryzae (moisture content: r = 0.928**; protein: r = 0.884** P<0.01), the percentage of perforated rice (moisture content: r = 0.872* P<0.05; protein: r = 0.945** P<0.01), and the percentage of rice powder (moisture content: r = 0.912**; protein: r = 0.951** P<0.01) during storage